If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10)(3x + -1) = 150 Reorder the terms: (10 + 2x)(3x + -1) = 150 Reorder the terms: (10 + 2x)(-1 + 3x) = 150 Multiply (10 + 2x) * (-1 + 3x) (10(-1 + 3x) + 2x * (-1 + 3x)) = 150 ((-1 * 10 + 3x * 10) + 2x * (-1 + 3x)) = 150 ((-10 + 30x) + 2x * (-1 + 3x)) = 150 (-10 + 30x + (-1 * 2x + 3x * 2x)) = 150 (-10 + 30x + (-2x + 6x2)) = 150 Combine like terms: 30x + -2x = 28x (-10 + 28x + 6x2) = 150 Solving -10 + 28x + 6x2 = 150 Solving for variable 'x'. Reorder the terms: -10 + -150 + 28x + 6x2 = 150 + -150 Combine like terms: -10 + -150 = -160 -160 + 28x + 6x2 = 150 + -150 Combine like terms: 150 + -150 = 0 -160 + 28x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-80 + 14x + 3x2) = 0 Factor a trinomial. 2((-8 + -1x)(10 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 2
Set the factor '(10 + -3x)' equal to zero and attempt to solve: Simplifying 10 + -3x = 0 Solving 10 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = 0 + -10 -3x = 0 + -10 Combine like terms: 0 + -10 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333Solution
x = {-8, 3.333333333}
| 3p+45=68 | | 1.5-2= | | (5w-1)(5+w)=0 | | (2x-3)+1=17 | | 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 | | 21x-28= | | h=-16t^2+16t+112 | | -3(x-1)+8(x-3)=6x-5x | | -5k-7=-37 | | p/2=3/4+p/3 | | x=9x^3-6x^2 | | y=10+-7(0) | | -k-3k-2k=-36 | | -z-4z=-65 | | 3/2x+1/5=3/4 | | y=10-7(-2) | | (0.1x-21)=180 | | 2a^5-8a^4-24a^3= | | 8.2-r=5r | | 15=35x |